2008
DOI: 10.1109/tgrs.2007.905974
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Waveform Encoding: A New Digital Beamforming Technique for Synthetic Aperture Radar Remote Sensing

Abstract: Abstract-This paper introduces the innovative concept of multidimensional waveform encoding for spaceborne synthetic aperture radar (SAR). The combination of this technique with digital beamforming on receive enables a new generation of SAR systems with improved performance and flexible imaging capabilities. Examples are high-resolution wide-swath radar imaging with compact antennas, enhanced sensitivity for applications like alongtrack interferometry and moving object indication, and the implementation of hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
237
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(258 citation statements)
references
References 44 publications
(62 reference statements)
1
237
0
Order By: Relevance
“…In addition to overcome the limitation, improving signal to noise ratio (SNR) and suppression range ambiguity should also be considered during SAR system design. Digital beamforming (DBF) on receive with a large receiving antenna in elevation in spaceborne SAR can form a sharp high gain scanning beam to receive radar echoes, and this method is named as the SCORE (SCan-On-REceive) technique [4][5][6][7]. Afterwards, the desired radar echoes arrive at the receiving antenna with a high antenna gain, while range ambiguities arrive at the receiving antenna with a low antenna gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to overcome the limitation, improving signal to noise ratio (SNR) and suppression range ambiguity should also be considered during SAR system design. Digital beamforming (DBF) on receive with a large receiving antenna in elevation in spaceborne SAR can form a sharp high gain scanning beam to receive radar echoes, and this method is named as the SCORE (SCan-On-REceive) technique [4][5][6][7]. Afterwards, the desired radar echoes arrive at the receiving antenna with a high antenna gain, while range ambiguities arrive at the receiving antenna with a low antenna gain.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the HRWS imaging capacity, multiple innovative spaceborne SAR imaging modes with the scheme of several sub-pulses transmitted with different time delays in a single pulse repetition interval (PRI) have been proposed in recent years [7][8][9][10][11][12]. The key point of processing SAR data of these modes is echoes separation corresponding to different sub-pulses [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the real price of spaceborne phased array radar and radar data generated with the available instrument technology of today is too high, affordable operational instruments will play a key role in the very near future. Multiple-input multiple-output (MIMO) radar system with multidimensional waveform encoding [13][14][15] is to employ multiple antennas for emitting several orthogonal waveforms which is better than traditional phased-array radar, but loosing coherent processing gain at the transmitting array. Recently, a compromise formulation between the coherent processing gain offered by the phased-array radar and the advantages of the MIMO radar, e.g., the waveform diversity, was proposed and named as Hybrid MIMO Phased Array Radar (HMPAR) [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Primary studies have demonstrated the potential advantages to simultaneously improve the performance of wide swath Synthetic Aperture Radar (SAR) imaging and ground moving target detection by utilizing multiple antennas both at transmission and reception [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Such an extension has been suggested for a variety of applications. A new notion of digital radar system combining waveform encoding on transmission with digital beamforming on reception is presented in [8], which is able to resolve the hitherto contradicting requirements for high resolution and wide coverage. The performance improvement for range resolution of SAR by multiple transmit and receive platforms with adequate cross-track displacement is investigated in [16], and the novel system concept for interferometric SAR based on MIMO configuration is proposed in [17].…”
Section: Introductionmentioning
confidence: 99%